Psychological Capital Profiles and Their Relationship With Internal Learning in Teams of Undergraduate Students - Geremias, Rosa Lutete; Lopes, Miguel Pereira; Soares, André Escórcio (Frontiers in Psychology, 2022)
Abstract This study aims to analyze the relationship between psychological capital profiles and internal learning in teams. The participants in this study were 480 undergraduate students. We performed a cluster analysis using the SPSS and yielded four distinct psychological capital profiles. The student profile with the highest scores in self-efficacy, optimism, hope, and resilience (Profile 2-Fully PsyCap) exhibited also the highest scores of internal learning in teams. On the other hand, the student profile with the lowest scores in self-efficacy, optimism, hope, and resilience (Profile 1- Empty PsyCap) presented the lowest scores of internal learning in teams. It is also noteworthy that there was no significant relationship between the profile with a positive combination between self-efficacy and hope (profile 4) and the profile that presents the optimism as the only positive psychological capability (profile 3), in the way they relate to internal learning in teams, which led us to reject the second hypothesis of the study. This study reinforces the role of psychological capital in academic settings and suggests that psychological capital profiles can affect internal learning in teams differentially.